Antimicrobial Resistance Issue: A Matter of Practice and Capacity to Conduct an Audit - Erni Juwita Nelwan (Interna Publishing, 2024)
The World Health Organization released the practical toolkit for antimicrobial stewardship in health-care facilities in low- and middle-income countries in 2019 due to increasing rates of antimicrobial resistance (AMR) causing the diminishing of treatment options and that the available antibiotics seem to no longer work. The introduction of this toolkit indicates the need to be more down-to-earth in combating the problems of antimicrobial resistance. This situation happened because we have taken antibiotics for granted for too long with less awareness, which results in the potential loss of its use and benefits. On the other hand, even though medicine is available, a major issue on the limited access to antibiotics are still reported in many parts of the world. The problem of antimicrobial resistance extended to the community; the population that is difficult to evaluate. In a hospital setting, patients are expected to be monitored which allows data to be gained easily. The commitment to combat resistance is demonstrated by the Indonesian government through the establishment of the National Committee of Antibiotics mentioned in Permenkes no. 8 (2015) that is located in each hospital and the upscaling of the issues of Antimicrobial Resistance to become one of the national priorities and program. In this issue, Fadrian, et al.7 conducted a study to measure the quality of antibiotics use at the western part of Indonesia. Every year between 18 to 24 November, we are celebrating the World AMR Awareness Week, with a strong hope to reduce the number of deaths which is at an estimate of 1.27 million people in 2019 who have been presumed to have died as a result to drug resistance. The hope must be followed by a strong commitment and understanding of the risk of overprescribing antibiotics, and if we ignore this, there will be a chance of a 9 times increase in mortality rates which translates to up to an estimate of 10 million deaths per year after 2050.